Democracy, culture, and the voice of poetry - Pinsky, Robert (University Center for Human Values series., 2002)
The place of poetry in modern democracy is no place, according to conventional wisdom. The poet is a casualty of mass entertainment and prosaic public culture, banished to the artistic sidelines to compose variations on insipid themes for a dwindling audience. Robert Pinsky argues that this gloomy diagnosis is wrongheaded and writes that to portray poetry and democracy as enemies is to radically misconstrue both. The voice of poetry, he shows, resonates with profound themes at the very heart of democratic culture. One of the country's most accomplished poets, Robert Pinsky served two terms as America's Poet Laureate (1997-2000) and led the immensely popular multimedia Favorite Poem Project, which invited Americans to submit and read aloud their favorite poems. Pinsky draws on his experiences and on characteristically sharp and elegant observations of individual poems to argue that expecting poetry to compete with show business is to mistake its greatest democratic strength--its intimate, human scale--as a weakness. He states that as part of the entertainment industry poetry will always be small and overlooked. As an art--and one that is inescapably democratic--it is massive and fundamental.